Effect of spirituality and ethics on green advertising, and the multi- mediating roles of green buying and green satisfaction - Tariq Jalees; Sahar Qabool; Syed Imran Zaman; Syed Hasnain Alam Kazmi (Cogent Business & Management, 2021)
This study has extended Motivation-Ability-Opportunity- Model and has developed a framework with seven variables (i.e., green brand, green satisfaction, green advertising, green buying behavior, and spirituality ethics. The study has taken a holistic approach by testing 15 relationships for understanding green marketing. The authors distributed 415 questionnaires to the students of selected universities of Karachi and received 395 filled-in questionnaires. The study's results support all the proposed hypotheses, and they are in line with earlier studies on green marketing (GM). The study found that green advertising (GA) is an essential aspect of green marketing (GM). Besides its direct effects on green-related elements (H1 to H7), it (green satisfaction) has significant mediating roles on ethics (ET) and green buying behavior (GBB) (H8); spiritually (SP) and green buying behavior (GBB) (H9); ethics, and green satisfaction (H10); Spirituality and green satisfaction (H11). We also found that green buying behavior mediates green advertising (GA) and green satisfaction (GS) (H12). Green buying behavior (GBB) also mediates green brand (GB) and green satisfaction (GS) (H13). The study's variable's interrelationships can be judged from the results that our results also support both multi mediating effects. The current study found that the multi-mediating impact of green advertising and green buying on ethics and green satisfaction (H14) and spirituality and green satisfaction (H15) is also significant. The theoretical and practical implications are based on empirical results.
Keywords: M30; M31; 650; Green marketing; consumer buying behavior; green advertisement; greenbrand; green satisfaction; spirituality; ethics